Analisis Aspek Sosial dan Politik Dalam Cerita Rakyat Paser “Peperangan di Sadurengas” Kajian Sosiologi Sastra : Analysis of Social and Political Aspects in the Paser Folktale “The War in Sadurengas “ A Study of Sociology of Literature - Ajeng Ratri Namdariah; Marwah Ulwatunnisa; Nina Queena Hadi Putri; Syaiful Arifin (Universitas Tidar, 2026)
This research has the aim to analyze the social and political aspects in Paser folklore through a literary sociallogy approach.. This study is based on the limited studies that explore regional folklore,especiallly from Paser,from a literary sociology perspective,considering that previous reserch tends to focus on contemporary literary works. The object of analsis includes the folklore “The War in Sadurengas”, which presents the local social and political dynamics. The apporoach applied is qualitative and descriptive.The data collection techniques used are literature study and document analysis. Furthmore,data presentatiom,and drawing conclusions by referring to indicators of social and political aspects. The main findings reveal thas the folklore “The War in Sadurengas” contains social elements such as social folklore “The War in Sadurengas”contains social elements such as social stratification,compliance with norms,social solidarity,and empathy values; as well as political elements in the form of power conflicts and elite political strategies.The results of study reinforce the view that folk tales can play a dual role: entertraining but also reflecting the social an political dynamics within society.Thus,the contribution of this reserch ecompasses two points: first,strengthening the sudy of literary sociology; second,untilizing folk tales as a learning tool based on local wisdom,emphasizing that folk tales do not merely function as entertainment,but also serve as a reflection of the social and political realities of society. Therefore,this study contributes to the strengthening of literary sociology studies as well as the use of folk tales as a learning medium based on local wisdom.